The dynamics of planned change; a comparative study of principles and techniques - Lippitt, Ronald; Watson, Jeanne; Westley, Bruce (New York, Harcourt, Brace, 1958)
The subject of this book is planned change - that is, change which derives from a purposeful decision to effect improvements in a personality system or social system and which is achieved with the help of professional guidance
oo 24/01/2019
Loans
Keywords: Change (Psychology)